The Impact of Servant Leadership on Proactive Service Behavior: a Moderated Mediation Model - Yinan Zhang; Yue Yin; Weilin Su (BMC Psychology, 2024)
Abstract As the implementers of government policies, junior civil servants bear the responsibility of providing services to the public. Whether they can put themselves in the people’s shoes and show more active service consciousness directly reflects the government’s management ability and the realization of service-oriented government goals. Although proactive service behavior has been studied, it has not been brought into the field of government administration. Hence, from the perspective of servant leadership, this study attempts to introduce proactive service behavior (PSB) into the field of government administration, and discusses the promotion strategies of junior civil servants’ PSB in China. Through the statistical analysis of 416 junior civil servants collected in the two stages, this study verifies that servant leadership has a significant positive impact on public service motivation and PSB of junior civil servants. Public service motivation (PSM) can partially mediate the promotion effect of servant leadership on junior civil servants’ PSB. Role identity can positively moderate the relationship between servant leadership and junior civil servants’ PSM, and then affect their PSB. Therefore, this study suggests that leading cadres should integrate servant leadership into daily life, take the lead in providing quality services to their subordinates, and then inspire more proactive service to the masses.